Managerial attributes and enterprise access to formal credit in Myanmar - Henrik Hansen; John Rand; Finn Tarp; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Using data from a new survey of small and medium-sized enterprises in Myanmar, we analyse enterprise demand for formal credit and the extent to which they are constrained in the formal credit market. We account for firms self-selecting out of the credit market in Myanmar. Our data contain information about individual firm owner/manager gender, managerial capacity, and attitude towards risk. We use this information to test whether the allocation of scarce loanable funds is systematically associated with these attributes. It emerges that managerial capacity and risk attitudes are positively associated with the probability of firms demanding credit, while firms with female owner/managers have lower probabilities of demanding credit. On the supply side we find no discernible links to any of the three traits, whereas firm's size and age have substantial impacts on the probability of obtaining credit. As such, the allocation of credit could improve if banks were better at identifying managers' managerial capacity and personality traits.
Keywords: G21; L25; L26; O16; O17; 330; formal credit; gender; managerial capabilities; Myanmar; personality traits